Gestational Weight Gain among Healthy Pregnant Women from Asia in Comparison with Institute of Medicine (IOM) Guidelines-2009: A Systematic Review - Priyanka Arora; Bani Tamber Aeri (Journal of Pregnancy)
In 1990, Institute of Medicine (IOM) recommended gestational weight gain (GWG) ranges for women in the United States primarily to improve infant birth weight. Changes in key aspects of reproductive health of women of child bearing age, a rising prevalence of obesity, and noncommunicable diseases prompted the revision of IOM guidelines in 2009. However, there is no such recommendation available for Asian women. This systematic review assesses the utility of IOM-2009 guidelines among Indian and other Asian pregnant women in terms of maternal and fetal outcomes. 624 citations were identified using PubMed and Google Scholar, out of which 13 were included. Prospective/retrospective studies of healthy Asian women with a singleton pregnancy which specifically examined fetal-maternal outcomes relative to IOM-2009 guidelines were included. Results. Majority of pregnant Indian women achieved less GWG than the recommendations whereas a mixed trend was noticed among the other Asian pregnant women. The most common fetal-maternal complications among the excessive GWG women were found to be macrosomia, large for gestational age and caesarean section followed by gestational diabetes and hypertension, whereas low birth weight, small for gestational age and preterm birth, was found to be associated with low GWG women. The findings highlight the need for appropriate GWG limits across the different body mass index levels specifically for Indians and other Asian population. However, there are not enough publications regarding the utility of IOM-2009 guidelines among the Indian and other Asian women. Thus, higher-quality researches are warranted in future to further validate the findings of the present review.